The Comparison of Outcome in Treating Proximal Ureteric Stones of Size 10 mm to 15 mm Using Extracorporeal Shock Wave Lithotripsy as Compared to Ureterorenoscopic Manipulation Using Holmium Laser (Journal of Renal and Hepatic Disorders, 2020)
Urinary stone disease or nephrolithiasis, the third most common disease of the urinary tract, is a major health issue due to its high prevalence, occurrence, and recurrence. The hallmark of a stone that obstructs the ureter or renal pelvis is excruciating, intermittent pain that radiates from the flank to the groin or to the inner thigh. Stone size influences the rate of spontaneous stone passage. Our aim was to compare the efficacy & the frequency of stone-free patients after intervention at 1 week after extracorporeal shock wave lithotripsy (ESWL) and ureterorenoscopic (URS) manipulation for proximal ureteric stone (10–15 mm size). This randomized control trial was done in the department of Urology, KRL Hospital Islamabad from 18th Nov 2019 to 18th May 2020. After meeting the inclusion criteria, 100 patients were enrolled and were divided into two groups. The first group was treated with ESWL and the other with URS. Then, procedures were done. Follow-up was noted after 1 week in the stone clinic. The average age of the patients was 39.71 ± 10.17 years. Efficacy in the ESWL group was found in 68% cases while in the URS group, efficacy was noticed in 76% cases (P > 0.05). Male patients were three times at a higher risk of recurrence as compared to females. This study concluded that both ESWL and URS are equally effective statistically in terms of the frequency of stone-free patients at 1 week for proximal ureteric stone (10–15 mm size).
Keywords: proximal ureteric stone; extracorporeal shock wave lithotripsy; ureterorenoscopic; manipulation; Endourology; Stoneclinic